If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y = 66 Solving 6x + 3y = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = 66 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = 66 + -3y 6x = 66 + -3y Divide each side by '6'. x = 11 + -0.5y Simplifying x = 11 + -0.5y
| -9x^2=6x^2 | | ln(x+37)=x | | 12x^2-113x+255=0 | | 3x/6-8=15 | | -y=-144 | | xy+yx=1 | | -5y-3=2y+12 | | 0.005669x^4+0x^3+0x^2-5x+858.468=0 | | 3x/5-3=21 | | -6-1x+12x=10x+6 | | 5x+11y=6x+3y | | 2x+5=8x-4 | | Abx^2-(a+b)x+1=0 | | 10(x-2)=12 | | 10(e-2)=12 | | 10(0-2)=12 | | 10+N+N=18 | | b=351655c-1x-1 | | 351655=bxc | | (5X+6)-(-3x+10)=2x-4 | | 3(x+3)-7=4(x-2)+5 | | 6(x+13)=7x-8-3x | | 0.009x+0.2(500-x)=0.03*500 | | 3Y-2Z=-5 | | 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 |